Edukasi dan Penerapan Latihan Metode Closed Kinetic Chain pada Kondisi Osteoarthritis Genu di Wilayah Puskesmas Mojolaban Sukoharjo - Kurnia Lutfi Farizqi; Farid Rahman; Eni Sulistyowati (Asosiasi Riset Ilmu Matematika dan Sains Indonesia, 2024)
Mojolaban is a sub-district located in Sukoharjo Regency. Osteoarthritis is one of the most common complaints experienced by elderly people in Mojolaban. Knee osteoarthritis is inflammation of the knee due to damage to the knee joint which can be caused by age or trauma. This condition causes pain, stiffness in the joints and limitations in movement in the knee. The aim of the physiotherapy program in cases of osteoarthritis is education and demonstration of exercise therapy in the form of closed kinetic chain exercises to reduce pain and prevent complaints from getting worse. The method used is the counseling method (lecture and question and answer), providing leaflets, education, and demonstrations about closed kinetic chain exercises related to osteoarthritis knee targeting participants at Bekonang RW 09 Elderly Posyandu. To evaluate the increase in understanding, the author used a questionnaire before and after the test. The results showed a significant increase in understanding of osteoarthritis material and exercise therapy, with the average score increasing from 2.25 on the pre-test to 4.35 on the post-test. It is hoped that the results of this Community Service activity will become a reference for physiotherapists and other health professionals to encourage the implementation of similar activities, so that they can improve public health, especially in cases of osteoarthritis genu in the elderly.